Combined Therapy with Traditional Chinese Medicine and Antiplatelet Drugs for Ischemic Heart Disease: Mechanism, Efficacy, and Safety - Zongliang Yu (Hindawi Limited, 2021)
Ischemic heart disease is a significant risk factor that threatens human health, and antiplatelet drugs are routinely used to treat cases in clinical settings. Chinese medicine for promoting blood circulation and removing blood stasis (PBCRBSCM) can often be combined with antiplatelet drugs to treat ischemic heart disease. PBCRBSCM can inhibit platelet adhesion, activation, and aggregation; moreover, PBCRBSCM in combination with antiplatelet drugs exerts antiplatelet effects. The mechanism is related to several factors, including the inhibition of platelet activation and aggregation, improvement of the hemodynamic status and coagulation function, and correction of metabolism and inflammation. PBCRBSCM can also regulate the absorption and metabolism of conventional antiplatelet drugs and protect the gastric mucosal epithelial cells against damage induced by conventional antiplatelet drugs. Randomized controlled trials have confirmed that PBCRBSCM preparations and the active ingredients in these preparations can reduce resistance to aspirin and clopidogrel so that the combination of these drugs can exert their antiplatelet effects. In the perioperative treatment of patients with stable angina pectoris, unstable angina pectoris, and acute coronary syndrome undergoing percutaneous coronary intervention therapy, preparations of the active ingredients of PBCRBSCM combined with antiplatelet drugs and other conventional Western medicine treatments have been proven effective. The efficacy and safety of such combinations have also been extensively verified. Considerable progress has been made to understand the antiplatelet mechanism of PBCRBSCM. However, most clinical studies had problems, such as limited sample size and inappropriate research design, which has limited the translational use of PBCRBSCM in antiplatelet therapy. A large-scale, multicenter, randomized controlled study with cardiovascular events as the endpoint is still to be conducted to provide evidence for the combined application of PBCRBSCM and antiplatelet drugs in the prevention and treatment of ischemic heart disease.